The role of transboundary air pollution over Galicia and North Portugal area - Borrego, C. (2018)
Insummer,highlevelsofozone(O3)arefrequently measured at both Galicia and Northern Portugal air quality monitoring stations, even exceeding the limit values imposed by legislation. This work aims to investigate the origin of these high O3 concentrations by the application of a chemical transport modelling system over the northwestern area of the Iberian Peninsula. The WRF–CHIMERE modelling system was applied with high resolution to simulate the selected air pollutionepisodesthatoccurredsimultaneouslyinGaliciaand North Portugal and in order to study both the contribution of local emission sources and the influence of transboundary pollution. Emission inputs have been prepared based on the development of the Portuguese and Galician emission inventories. The obtained results for O3 have been evaluated and validated against observations. Modelling results show possiblecontributionofthetransboundarytransportovertheborder of two neighbour regions/countries, indicating that the O3 episode starts over the urban and industrialised area of North coast of Portugal, reaching the maximum peaks over this region; at the same time, O3 levels increased over Galicia region, where lower concentrations, but still high, were observed. These results pointed out that air quality management should not be driven by political boundaries and high light the importance of joining efforts between neigh bouring countries.